Argon Ion Irradiation Effect on the Magnetic Properties of Fe-Al2O3 Nano Granular Film - Purwanto, Setyo; Sakamoto, Isao (Makara Journal of Technology, 2014)
We studied the effect of Argon (Ar) ion irradiation on Fe-Al2O3 nanogranular thin film. X-ray diffraction (XRD) patterns show that the ion dose might promote the growth of the Fe2O3 phase from an amorphous phase to a crystalline phase. The magnetic and magnetoresistance properties were investigated using a vibrating sample magnetometer (VSM) and a four point probe (FPP). The results suggest that percolation concentration occurred at the 0.55 Fe volume fraction and with a maximum magnetoresistance (MR) ratio of 3%. The present MR ratio was lower than that of previous results, which might be related to the existence of the α-Fe2O3 phase promoted by Ar ion irradiation. CEMS spectra show ion irradiation induces changes from superparamagnetic characteristics to ferromagnetic ones, which indicates the spherical growth of Fe particles in the Al2O3 matrix.